PENGEMBANGAN SISTEM INFORMASI PENGOLAHAN PAJAK PADA BIDANG PAJAK DAERAH HOTEL DAN RESTAURANT DI DINAS PENDAPATAN DAERAH KOTA BANDUNG - Yelli Eka Sumadhinata (Bina Ekonomi, 2010)
From beginning  autonomy  region now, every  region must have  to develop  ability get source income  region  for expenditure  APBD and which one with use maximum  tax assignment  region. For then needed a new system development to encode for processing on computer tax region and to increase service towards public. This  research  intend  for knowing everything about excellent  foundation income tax region and how  to processing data from obligation  tax  report, when  tax obligation  from  they tax and doing  registration,  fill up SPTPD  after processing will persistent value  tax  region must pay  for hotel and restaurant. Afterwards SPTPD to encode for processing on computer then result data mold form SKPD. Mold SKPD will give to obligation tax and can do payment with bring SKPD for get SSPD all of them will encode for processing with use language program Borland Delphi version 7.0 and for save database use SQL SERVER 2000. Result  this  research  showed  that system working  as of precisely  comply with a request service  public, however a lot of tax obligation  feel decrease  concept mechanism  reporting,  process  and pay for  tax obligation  until enthusiastic society community  less.